The accuracy of cone-beam computed tomography in the evaluation of boney support of teeth among patients with a unilateral cleft of lip and palate among IraqiPopulation - Kadhim, Sahar SH (Journal of Baghdad College of Dentistry, 2019)
Background: To evaluate the bony supports of the teeth adjacent to the area of cleft in patient with unilateral cleft lip and palate and to compare these measurements with the measurements of the same teeth in non-cleft side by using CBCT. Materials and methods: The CBCT scans of 30 patients having cleft lip( unilateral) and palate(unilateral), were analyzed and the measurements of the alveolar bony support for teeth that are adjacent to the cleft area were measured with those teeth located on opposite side (non- clef) side. For each tooth, the measurements will taken for the distance between the( cementoenamel junction) (CEJ) and the bony crest (AC) at the( buccal area) was measured and the thickness of the buccal plate At zero, one, two, and four mm. Results: The thickness of the bony support of central incisor at zero and one mm apically were statistically significantly thinner in cleft regions than in the non cleft regions. The CEJ-AC distance of the central teeth that are adjacent to the area of cleft was higher significantly than those for non-cleft area. For the canine teeth at 0, 1, 2, and 4mm apically were similar to those results obtained for central teeth at 0 and 1mm levels. Also, the CEJ-AC distance of the canine teeth that are adjacent to the cleft area was higher significantly than those for non-cleft area. Conclusion: person with unilateral cleft lip and palate showed a reduced alveolar bony support of the teeth located adjacent to the area of cleft when compared with the controls and This will cause a lot of problems in the future, so professional dental control is very essential for the maintaining of good periodontal health for those patients